Cue utilisation reduces effort but increases arousal during a process control task. (May 2018) - Wiggins, Mark W.; Whincup, Edward; Auton, Jaime C.
Abstract: Process control environments are characterised by rapid changes in work demands, the successful response to which is dependent upon the availability of cognitive resources. Since high cue utilisation is associated with a reduction in cognitive load and a consequent release of residual resources, it was hypothesised that participants with high cue utilisation would experience lower subjective arousal and lower physiological effort in response to increases in the work demands associated with a simulated rail control task. A total of 41 participants completed a 10 min, low work demand period, followed by a 10 min, high work demand condition. High cue utilisation was associated with a reduction in systolic blood pressure and the maintenance of sustained, superior performance in response to high work demands. However, an increase in subjective arousal was also evident. The outcomes have implications for the selection and assessment of operators of high reliability, dynamic, process control environments. Highlights: High cue utilisation is associated with high levels of performance during a simulated rail control task. Low cue utilisation is associated with higher systolic pressure during higher work demands. High cue utilisation is associated with higher arousal during higher work demands. High cue utilisation is associated with higher performance, lower effort, and greater attention to changes in task demands.